Integrated output filter inductor for permanent magnet motor drives - Raza Khowja, Muhammad; Gerada, C.; Vakil, Gaurang; Wheeler, Patrick; Patel, Chintanbai (2016)
This paper presents a novel approach to integrate the output filter inductor in permanent magnet synchronous motor (PMSM) drive system. The integrated output filter inductor is based on utilizing the motor magnetics as a filter inductance instead of introducing a separate filter inductor. Thus, eliminating added filter inductor losses and associated weight and volume. The vector controlled model, taking modulation and switching effect in to account, has been developed using MATLAB/Simulink tool for the proposed integrated output filter inductor. The currents obtained from MATLAB/Simulink model are then injected into the Finite Element model to validate the concept. The performance of the proposed and conventional system is analyzed in terms of mean electromagnetic torque, torque ripple, motor losses, inductor losses, weight and volume